Impact of Soil Test Based Fertilizer Application on Yield, Soil Health and Economics in Rice - Jayalakshmi, M.; Prasadbabu, G.; Chaithanya, B. H.; Bindhupraveena , R.; Srinivas, T. (Indian Journal of Extension Education, 2021)
Frontline demonstrations were carried out to study the soil test-based fertilizer application on yield, soil health and economics in rice during the kharif seasons of 2017, 2018 & 2019 in farmers’ fields of Kurnool district of Andhra Pradesh. The demonstrations conducted in ten locations revealed that application of nitrogen, phosphorus and potassium based on soil test values resulted in an average yield increase of 5.01 per cent over the farmer’s practice. Demonstration plots recorded an average B: C ratio of 2.9 against farmers’ practice of 2.4 and the technology index reduced from 3.84 to 1.53 per cent. The organic carbon content increased from 0.45 to 0.50 per cent due the application of farmyard manure based on soil test value. The soil test based fertilizer application resulted in higher yield, net returns, B:C ratio and organic carbon content and low technology index indicates the feasibility of technology to adopt at farmers’ level.
Keywords: Rice; Soil test based fertilizer application; Technology gap; Extension gap; Technology index